Analysis Of The Effect Of Organizational Transformation Of Pt. Pln (Persero) On Turnover Intention With Employee Engagement As Mediation - Putra, Yoko Aldino; Partiwi , Sri Gunani (Journal Research of Social Science, Economics, and Management, 2025)
Rapid organizational transformation at PT PLN (Persero) has had various impacts on employees, especially those who have worked in an area for a long time. Sudden transfers to other areas far from their previous residences have caused many employees to have difficulty adapting. Employees who have built family lives in their home areas feel a loss of stability and comfort, which has an impact on decreasing work enthusiasm. This change also creates a great emotional burden, especially for employees who have to leave their families to carry out duties in new locations. This study can provide important information regarding the conditions of organizational change carried out by PT PLN (Persero) and its impact on turnover intention along with recommendations for improvements that can be taken to improve existing conditions. The recommendations given can be used as considerations in compiling preventive and corrective programs to reduce employee turnover intention. This study uses the structural equation modeling analysis method with the help of the SmartPLS 4.0 program.